Does gut microbiota dysbiosis impact the metabolic alterations of hydrogen sulfide and lanthionine in patients with chronic kidney disease? - Yuselys Garcia-Martinez; Elena Alexandrova; Valerio Iebba; Carlo Ferravante; Michelle Spinelli; Gianluigi Franci; Angela Amoresano; Alessandro Weisz; Francesco Trepiccione; Margherita Borriello; Diego Ingrosso; Alessandra F. Perna (BMC Microbiology, 2024)
Abstract Background Chronic Kidney Disease (CKD) is characterized by a methionine-related metabolic disorder involving reduced plasma levels of hydrogen sulfide (H2S) and increased lanthionine. The gut microbiota influences methionine metabolism, potentially impacting sulfur metabolite dysfunctions in CKD. We evaluated whether gut microbiota dysbiosis contributes to H2S and lanthionine metabolic alterations in CKD. Methods The gut microbiota of 88 CKD patients (non-dialysis, hemodialysis, and transplant patients) and 26 healthy controls were profiled using 16 S-amplicon sequencing. H2S and lanthionine concentrations were measured in serum and fecal samples using the methylene blue method and LC-MS/MS, respectively. Results The CKD population exhibited a tenfold increase in serum lanthionine associated with kidney dysfunction. Despite lanthionine retention, hemodialysis and transplant patients had significantly lower serum H2S than healthy controls. Fecal H2S levels were not altered or related to bloodstream H2S concentrations. Conversely, fecal lanthionine was significantly increased in CKD compared to healthy controls and associated with kidney dysfunction. Microbiota composition varied among CKD groups and healthy controls, with the greatest dissimilarity observed between hemodialysis and transplant patients. Changes relative to the healthy group included uneven Ruminococcus gnavus distribution (higher in transplant patients and lower in non-dialysis CKD patients), reduced abundance of the short-chain fatty acid-producing bacteria Alistipes indistinctus and Coprococcus eutactus among transplant patients, and depleted Streptococcus salivarius in non-dialysis CKD patients. A higher abundance of Methanobrevibacter smithii, Christensenella minuta, and Negativibacillus massiliensis differentiated hemodialysis patients from controls. No correlation was found between differentially abundant species and the metabolic profile that could account for the H2S and lanthionine alterations observed. Conclusions The metabolic deregulation of H2S and lanthionine observed in the study was not associated with alterations in the gut microbiota composition in CKD patients. Further research on microbial sulfur pathways may provide a better understanding of the role of gut microbiota in maintaining H2S and lanthionine homeostasis.